Ancient drama as a therapeutic tool The theatrical performances by inpatients at the Dromokaiteion Hospital in the 1960s: The performance of Aeschylus' Eumenides in 1965 - Bostantzis, Triantafyllos (Education & Theatre, 2023)
In the 1960s, a pioneering method of group psychotherapy – based on ancient drama – was applied at the Dromokaiteion Psychiatric Hospital by psychiatrist Dr. George Lyketsos. During the therapeutic process, the participating inpatients were taught ancient drama and took active part in rehearsals with the aim of presenting performances of ancient Greek tragedies. The present article attempts to outline the psychotherapeutic method followed by Lyketsos from 1960 to 1965, with reference to the 1965 performance of Aeschylus’ Eumenides, in which long-term inmates at the Dromokaiteion participated as actors. In addition, the article attempts to identify the “Lyketsos method” in relation to the wider field of drama therapy, while aiming to trace any elective affinities with Jacob Moreno’s “psychodrama”.